1993
DOI: 10.1177/074873049300800101
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and the Mammalian Circadian System: I. In Vitro Phase Shifts by Serotonergic Agonists and Antagonists

Abstract: The primary mammalian circadian clock, located in the suprachiasmatic nuclei (SCN), receives a major input from the raphe nuclei. The role of this input is largely unknown, and is the focus of this research. The SCN clock survives in vitro, where it produces a 24-hr rhythm in spontaneous neuronal activity that is sustained for at least three cycles. The sensitivity of the SCN clock to drugs can therefore be tested in vitro by determining whether various compounds alter the phase of this rhythm. We have previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(98 citation statements)
references
References 58 publications
6
92
0
Order By: Relevance
“…Highly consistent with this hypothesis are other experiments that showed that 5-HT may regulate the expression of GFAP and of its encoding message in vitro (Le Prince et al, 1990), potentially through astroglia 5-HT 1A receptors (Whitaker- Azmitia et al, 1993) and release of the neurotrophic agent S-100␤ (Whitaker- Azmitia et al, 1990Azmitia et al, , 1993. Accordingly, 5-HT1A receptors are expressed in the SCN (Prosser et al, 1993) that also exhibits S-100 immunoreactivity (Bosler, unpublished observations;Brezun and Daszuta, 1999).…”
Section: Serotoninergic Fibers As Potential Relays For Corticosteronesupporting
confidence: 62%
“…Highly consistent with this hypothesis are other experiments that showed that 5-HT may regulate the expression of GFAP and of its encoding message in vitro (Le Prince et al, 1990), potentially through astroglia 5-HT 1A receptors (Whitaker- Azmitia et al, 1993) and release of the neurotrophic agent S-100␤ (Whitaker- Azmitia et al, 1990Azmitia et al, , 1993. Accordingly, 5-HT1A receptors are expressed in the SCN (Prosser et al, 1993) that also exhibits S-100 immunoreactivity (Bosler, unpublished observations;Brezun and Daszuta, 1999).…”
Section: Serotoninergic Fibers As Potential Relays For Corticosteronesupporting
confidence: 62%
“…Binding sites for several 5-HT receptor subtypes have been reported in the SCN, including the 5-HT 1A , 5-HT 1B , 5-HT 2A , 5-HT 2C , and 5-HT 7 receptors (Sumner et al, 1992;Manrique et al, 1993;Prosser et al, 1993;Miller et al, 1997). However, the functional organization and subcellular localization of 5-HT receptor subtypes in the SCN are not well understood.…”
Section: Abstract: Circadian Rhythms; Serotonin; 5-ht 1b Receptor Knmentioning
confidence: 99%
“…Coronal brain slices (500 μm) containing the SCN were prepared during the daytime from adult, male C57BL/J6 mice, housed in 12:12 LD conditions, as reported previously (Prosser and Gillette, 1989;Prosser et al, 1993;Prosser, 1998). Slices were prepared between Zeitgeber time (ZT) 0-4 (where ZT 0 = lights-on and ZT 12 = lights-off in the donor animal colony).…”
Section: Brain Slice Preparationmentioning
confidence: 99%